THE EFFECTS OF SOCIAL MEDIA USE AND ACADEMIC PROCRASTINATION ON STUDENTS’ LEARNING MOTIVATION - Fera Fitrianingsih; Edris Zamroni; Richma Hidayati (PT Altin Riset Publishing, 2026)
This study aims to analyze the relationship between social media use and academic procrastination and the learning motivation of students at State High School 1 Mejobo, Kudus. The study employed a quantitative approach with an ex post facto correlational design. The study population consisted of 1,061 students in grades 10, 11, and 12, with a sample of 290 students selected using stratified random sampling. Data were collected via a four-point Likert-scale questionnaire that had undergone validity and reliability testing. Data analysis was performed using multiple linear regression with SPSS 23.0, after meeting the criteria for normality, heteroscedasticity, and multicollinearity. The results indicate that social media use is positively and significantly associated with learning motivation (B = 0.163; t = 3.259; p = 0.001). Academic procrastination also shows a positive and significant relationship with learning motivation (B = 0.313; t = 6.315; p < 0.001). Taken together, these two variables produced a significant model (F = 40.300; p < 0.001), with an R² value of 0.529. Thus, social media use and academic procrastination collectively explain 52.9% of the variation in students’ learning motivation. These findings underscore the importance of understanding digital behavior and the management of academic tasks in a contextual manner when developing strategies to enhance learning motivation.